Reappraisal of a historical porfimer sodium photodynamic therapy study for vascular restenosis: Efficacy, high procedural mortality, and methodological insights from a rabbit balloon-injury model - Ai-Hsien Adams Li; Yuan Hung Liu; Ya-Hui Tsai; Chi-Yu Yang; Kuan-Ming Chiu (PLoS ONE, 2026)
Background Restenosis driven by intimal hyperplasia remains a major limitation of peripheral arterial intervention. Photodynamic therapy (PDT) using porfimer sodium (Photofrin®) demonstrated promising preclinical efficacy in the 1990s; however, its translation into clinical vascular practice has been stalled. We reappraised a historical pilot dataset to evaluate both biological efficacy and procedural feasibility. Methods In a rabbit model of bilateral femoral artery balloon injury (10 animals initiated), one artery per animal received intraluminal PDT (630 nm, ~ 5.6 J/cm²) 48 h after intramuscular porfimer sodium administration (2 mg/kg), while the contralateral artery served as an internal control. Histomorphometric analysis of the intima-media ratio (IMR) was performed 21 days after injury. Results The procedural feasibility of this approach is severely limited. Only three of the ten animals yielded analyzable paired arterial samples because of high intraoperative mortality (40%) and postoperative complications. In surviving animals, PDT-treated arteries demonstrated a consistent and marked suppression of neointimal hyperplasia compared with controls (IMR 0.29 ± 0.07 vs. 1.65 ± 0.55; P < 0.001 ), corresponding to a median IMR reduction of 82%. Conclusions This reappraisal confirms the potent biological effects of porfimer sodium-mediated PDT on neointimal hyperplasia. However, the principal contribution of this study lies in the transparent documentation of critical translational barriers, particularly the unsustainable procedural mortality associated with this model of bilateral injury. By providing detailed dosimetry parameters and a candid feasibility analysis, this study offers methodological insights to guide the design of safer and more translatable preclinical vascular PDT studies in the future.